Spatial Dynamics and Ecological Risk Assessment of Microplastics in Littoral Sediments of the Sea of Marmara, Türkiye - Esra Billur Balcıoğlu İlhan (Journal of Marine Science and Engineering)
Plastic and especially microplastic (MP) pollution has posed a serious threat to the marine environment for decades. Studies on MPs have started to gain momentum especially in the Sea of Marmara (SoM), which is an international waterway, under the pressure of intense maritime traffic and exposure to domestic and industrial discharges. The aim of this study was to evaluate the MPs found in surface sediments collected from the coastal area of the SoM according to the locations and to reveal the extent of the existing pollution. This is the first study to examine MPs in both the surface sediments of the entire shorelines of the SoM, which have not been previously reported, and in the surface sediments of Çanakkale Strait. Accordingly, the highest MP abundance was detected at Yenice station (St 15) with 1286 items/kg, and the lowest MP abundance was detected at Turan Village station (St 14) with 199 items/kg. The most dominant shapes across all sampling stations and months were fiber (37%) and fragment (26%), while the most dominant color was blue (35%). According to the polymer characterization results, PE (polyethylene) was found to be the most dominant polymer type. Additionally, most stations were found to have “Moderate” and “High” pollution levels in terms of the contamination factor (CF), and regions were classified as “Moderate” and ‘High’ in terms of the pollution load index (PLI), with the St 15 station specifically exhibiting “Very High” pollution levels. Furthermore, hazard index (HI) and pollution risk index (PRI) values were also calculated regionally, revealing that regions have pollution levels classified as “High”, “Very High”, and even “Dangerous”. This study concluded that there are no areas with low pollution levels in SoM, and that the threat posed by MP pollution in this sea is increasing. Furthermore, this study found that stations with high MP pollution levels are located near river discharges and that rivers significantly contribute to MP pollution in the seas. The findings are of great importance in terms of the need to implement sustainable plans and measures to prevent pollution in the SoM and to take concrete steps to protect and ensure the sustainability of coastal ecosystems, particularly those under serious pollution threats.